Mesenchymal Stem Cells Isolation, Characterization and Applications - Van Pham, Phuc (IntechOpen, 2017)
Mesenchymal Stem Cells: Isolation, Characterization, and Applications thoroughly presents the isolation, characterization, and some applications of mesenchymal stem cells in the clinic. The book has two parts: "Isolation and Characterization" and "Clinical Perspectives and Applications." In Part I, the subsequent chapters introduce some techniques in isolation, characterization, and purification of mesenchymal stem cells in different tissues. In Part II, some applications of mesenchymal stem cells in the popular diseases, which include cartilage regeneration, spinal cord injury, and osteoarthritis, are discussed. This book provides a succinct yet comprehensive overview of mesenchymal stem cells for advanced students, graduate students, and researchers.